Assessing The Suitability Of The Content And Construct Of The End-Of-Semester Exams For English Class VII MTS PUTRA-PUTRI SIMO According To The 2013 Curriculum - Huda, Samsul Huda (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
This study focuses on the analysis of multiple choice test questions that measure critical thinking and tests of procedural knowledge of grammar material for introductory (beginner) English courses. Sample analysis includes:(1) item difficulty, (2) item differentiation, (3) item validity, and (4) item reliability. To measure the difficulty, a comparison formula is used for the number of respondents who answered correctly versus the number of respondents who answered incorrectly. The Pearson product-moment test is used to measure the validity and uniqueness of the item. The Cronbach alpha test is then used to determine the reliability of the test. The results of the difficulty test classify the test items into